The Global Challenge of Child Injury Prevention - Sleet, David (International journal of environmental research and public health, 2018)
According to Margaret Chan, former Director General of the World Health Organization (WHO), and Ann Veneman, former Executive Director of the United Nations Children’s Fund [1]: Once children reach the age of five years, unintentional injuries are the biggest threat to their survival. According to a recent analysis of annual publication in infant, child and adolescent child injury conducted by Lawrence [7] using the SafetyLit database of citations not listed in Medline [8], he uncovered a total of 55,467 publications from 1966–2017, and 26,648 publications from 1966–1997 compared with Glied’s 187 publications during the same period (1966–1997). According to Dr. Sabastian Van As, who heads the trauma unit at the Red Cross War Memorial Children’s Hospital in Cape Town, South Africa, “The world is a dangerous place for children … even more so in poor countries. According to the 2013 Global Burden of Disease Study [23] road traffic injuries were the leading cause of death among adolescents around the world.